Wage Formation Under Low Inflation - Steinar Holden (Norges Bank, 2004)
This paper reviews the literature on the effects of low steady-state inflation on wage formation, focusing on four different effects. First, under low inflation, downward nominal wage rigidity (DNWR) may prevent real wage cuts that would have happened had inflation been higher. Second, wages (and prices) are given in nominal contracts, and inflation affects both how often wages are adjusted, and to what extent wages are set in a forward-looking manner. Third, incomplete labour contracts may provide workers with scope for inflicting costs on the firm without violating the contract, thus forcing the firm to accept a rise in nominal wages. Fourth, if effort depends on wages relative to a reference level, and workers and firms underweight inflation when updating the reference level, positive but moderate inflation may reduce wage pressure. The paper ends by a brief survey of empirical evidence, and a discussion of whether labour markets may adapt to a low inflation environment.
hdl:11250/2498540
Keywords: J5; J3; E31; 330; wage formation; nominal contracts; downward nominal wage rigidity; inflation